Lipid Peroxidation in Brain Injury (Experimental Study) - V. N. Yelsky; S. V. Zyablitsev; Ye. D Yakubenko; M. S. Kishenya; S. V. Pishchulina; A. V. Yelsky (Общая реаниматология)
Objective: to study the general mechanisms responsible for the formation and stepwise development of the endogenous intoxication syndrome in the injury. Material and methods. One hundred and thirty animals with experimental brain injury (a blow upon the calvarium delivered by a free weight falling) were examined to study the pro- and antioxidant systems, the enzymatic activity in the blood and brain tissue homogenates; the markers of endogenous intoxication, such as medium-weight molecules, were determined. According to the neurological deficit scale developed by A. Ya. Yevtushenko (1989), the animals were divided into 2 groups: 1) those with a good (compensated) posttraumatic course and 2) those with a poor (decompensated) one. A package of the applied statistical programs «STADIA.6.1/prof» and «STATISTIKA» was employed. Results. Brain injury was used as an example to show how the posttraumatic endogenous intoxication syndrome developed. The latter developed on the cascade principle with the stepwise involvement of the homeostatic systems and with the more aggravated injury. The syndrome is determined by the initiation of processes of lipid peroxidation with the accumulation of its products and by the exhausted spares of antioxidant systems. This leads to hyperenzymemia (the enhanced activity of cathepsin D, acid phosphatase in the brain tissues and blood) and to the blood accumulation of toxic substances (medium-weight molecules) (toxemia). Key words: posttraumatic endogenous intoxication syndrome, lipid peroxidation, brain injury.